Exploration of plant growth-promoting endophytic bacteria from the crops grown in sodic soils (Bangladesh Journal of Botany, 2022)
Isolation of the potential endophytic bacteria from plants that are grown in sodic soils, their diversity and screening their plant growth-promoting activities for testing their efficiency as bio inoculants for the problem soils were studied. Twelve different isolates were selected out of 35 endophytic bacterial isolates on the basis of their richness in the endophytic population of different crop plants and the nucleotide sequences of 16S rRNA genes were observed. The endophytic bacteria for their plant growth-promoting traits such as nitrogen fixation, IAA production, ACC deaminase production, phosphate solubilization, siderophore secretion and antifungal activity were assessed. The best performing strains were evaluated using principal component analysis (PCA). The phylogenetic tree from the endophytic bacterial isolates of different crops grown in sodic soil was categorized into three clusters i.e. Firmicutes, β-Proteobacteria and γ- Proteobacteria. The PCA results identified two potential endophytic strains viz., Ma11 (Bacillus mojavensis) and Ri 2 (Pseudomonas fluorescens) from sodic soil-grown crops. The present findings revealed that the isolates, Ma 11 and Ri 2 were capable of improving crop growth under sodicity. These multifaceted endophytic bacterial isolates would be developed as new inoculants which will be highly suitable for sodic soils.Bangladesh J. Bot. 51(2): 271-280, 2022 (June)